ANALISIS COMPETITIVE ADVANTAGE MELALUI PENDEKATAN RELATIONAL CAPITAL DAN SUPPLY CHAIN INTEGRATION - Kusdi Raharjo; Agatha Christhy Wahyono (Politeknik Ubaya, 2021)
This research aims to examine the effect of relational capital to competitive advantage through supply chain integration. Research method in this study was explanatory research with a quantitative approach. This Research method used explanatory research with a quantitative approach. The object of this research was in four districts of East Java at Nganjuk, Kediri, Malang and Probolinggo which are centers of onion production that have the similar environmental conditions. The sampling method in this study used multistage proportional random sampling. There were 200 respondents as a sample of this research. Data analysis usedpath analysis method by software SPSS 23. The results showed that the relational capital has a positive but not significant effect on the supply chain integration and relational capital has a positive and significant effect on the competitive advantage